Combined QM/MM Study of Thyroid and Steroid Hormone Analogue Interactions with αvβ3 Integrin - Freindorf, Marek (Hindawi Publishing Corporation, 2012)
Recent biochemical studies have identified a cell surface receptor for thyroid and steroid hormones that bind near the arginine-glycine-aspartate (RGD) recognition site on the heterodimeric αvβ3 integrin. To further characterize the intermolecular interactions for a series of hormone analogues, combined quantum mechanical and molecular mechanical (QM/MM) methods were used to calculate their interaction energies. All calculations were performed in the presence of either calcium (Ca(2+)) or magnesium (Mg(2+)) ions. These data reveal that 3,5′-triiodothyronine (T(3)) and 3,5,3′,5′-tetraiodothyroacetic acid (T(4)ac) bound in two different modes, occupying two alternate sites, one of which is along the Arg side chain of the RGD cyclic peptide site. These orientations differ from those of the other ligands whose alternate binding modes placed the ligands deeper within the RGD binding pocket. These observations are consistent with biological data that indicate the presence of two discrete binding sites that control distinct downstream signal transduction pathways for T(3).